2021
DOI: 10.1101/2021.07.01.450810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimized nickase- and nuclease-based prime editing in human and mouse cells

Abstract: Precise genomic modification using prime editing (PE) holds enormous potential for research and clinical applications. Currently, the delivery of PE components to mammalian cell lines requires multiple plasmid vectors. To overcome this limitation, we generated all-in-one prime editing (PEA1) constructs that carry all the components required for PE, along with a selection marker. We tested these constructs (with selection) in HEK293T, K562, HeLa and mouse embryonic stem (ES) cells. We discovered that PE efficie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…The pAIO-PE3 plasmid, combined with a puromycin selection showed a significant increase compared to the regular PE3 system in mouse stem embryonic stem cells, with edit efficiencies ranging between 1.7% and 85%. In line with other ncRNA-dependent PE systems, pAIO-PE3 activity however also resulted in a high rate of indel/SNVgeneration for most loci, occurring in up to 90% of the clones [6] . Since PE3 systems are accompanied by higher undesired indels/SNVs, improved versions of ncRNA-independent PE systems would be safer alternatives for gene-editing in iPSC-derived models.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…The pAIO-PE3 plasmid, combined with a puromycin selection showed a significant increase compared to the regular PE3 system in mouse stem embryonic stem cells, with edit efficiencies ranging between 1.7% and 85%. In line with other ncRNA-dependent PE systems, pAIO-PE3 activity however also resulted in a high rate of indel/SNVgeneration for most loci, occurring in up to 90% of the clones [6] . Since PE3 systems are accompanied by higher undesired indels/SNVs, improved versions of ncRNA-independent PE systems would be safer alternatives for gene-editing in iPSC-derived models.…”
Section: Introductionmentioning
confidence: 76%
“…The few studies that tested multi-plasmid PE3 for editing in hiPSC showed a nearly undetectable edit efficiency [4] , making it not suitable for the generation of iPSC-derived disease models. However, the recently published PEA1 (pAIO-PE3) all-in-one plasmid was able to increase the edit efficiency significantly in immortalized cell lines as well as mouse embryonic stem cells (mESC) when combined with a puromycin selection step [6] . It did however induce similarly high unintended alterations as seen in the multi-plasmid approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R1 Mouse embryonic stem cells were cultured and transfected as described by Adikusuma et al . (2021) 67 without modification.…”
Section: Methodsmentioning
confidence: 99%
“…Complementary gRNA oligos were designed with overhangs facilitating golden gate assembly and cloned into pSpCas9(BB)-2A-Puro (PX459) V2.0 (Addgene plasmid #62988) according to Ran et al (2013) 64 . R1 Mouse embryonic stem cells were cultured and transfected as described by Adikusuma et al (2021) 66 without modification.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%